From Tibet to India and further : transit journeys and onward-migration aspirations of tibetan-born Tibetans in Dharamsala - Frilund, Rebecca (fi=Turun yliopisto|en=University of Turku|, 2019)
In this PhD dissertation, I explore the migratory settings, processes and aspirations of the Tibetans who have migrated from Tibet via Nepal to Dharamsala, a town in the Indian Himalayas. The main overall research questions are: what kind of migratory setting does Dharamsala have; what are the major triggers or drivers of the Tibetans to migrate to Dharamsala; how are their migration histories or journeys to India represented; and how do their onward-migration aspirations actualise in situ in Dharamsala. I also pay attention to the active agency of the Tibetan-born interviewees of this study. I used ethnographic methods, such as observations and interviews; the majority of the fieldwork was conducted in Dharamsala where I stayed around ten months between the years 2009–2015. Dharamsala is a home of around 14,000 Tibetans, including their religious leader, the 14th Dalai Lama. The Government of India allowed Tibetans to establish the headquarters of the Central Tibetan Administration (CTA) in Dharamsala after the Dalai Lama escaped to India with his retinue in 1959 as the Peple’s Republic of China (PRC) had occupied Tibet. India has also allowed the CTA to govern the Tibetan diaspora communities in the country rather autonomously. As Dharamsala is considered the capital of the Tibetan diaspora and numerous Tibetan-run non-governmental organisations have their headquarters in town, it was an informative place to conduct fieldwork; besides the fact that Tibetans migrate there from Tibet and the newcomers often stay in town, it is a scene for various types of out-migration activities. Hence, different types of mobilities encounter each other in Dharamsala. This PhD dissertation offers a novel example of transit migration type of migration in the context of Tibetan-born Tibetans. It explored their migration from various yet complementary theoretical and conceptual viewpoints, most importantly from the angles of transit migration, refugee or forced migrant journeys and postcolonial studies on migration with an emphasis on postcolonial geography of migration. As their migration has not been studied from these perspectives before, the dissertation offers novel theoretical and conceptual insights which are meant to be applicable also when exploring transit migration type of migration among other minorities or refugees in the Global South. The findings demonstrate that the journey of Tibetan-born Tibetans via Nepal to India can be considered as transit migration and that their difficult journey over the Himalayas tends to have an important collective meaning for the diaspora Tibetans in general. It is also very common for Tibetan-born Tibetans to migrate, or aspire to migrate, onwards from India particularly because of the difficulties that they face there. However, this is a more complex phenomenon as they come to India in order to see the Dalai Lama who is banned by the People’s Republic of China (PRC), seek education from the Tibetan premises and find opportunities that are not available in Tibet, not only in order to migrate further. Hence, Dharamsala hosts organisations, which assist Tibetans from Tibet in India but also provide qualifications for them to migrate further by teaching them English and other foreign languages, for instance. Finally, it is demonstrated that unequal (post)colonialism-related power structures, such as unequal distribution of wealth or limited access to mobility and opportunities, manifest in the Tibetan migration to India and onwards.

Väitöskirjatutkimukseni käsittelee Tiibetistä Nepalin kautta Intian Himalajalla sijaitsevaan Dharamsalan kaupunkiin saapuneiden tiibetiläisten muuttoliikettä ja haaveita muuttaa eteenpäin. Kysyn väitöskirjatutkimuksessani, mikä on saanut haastattelemani tiibetiläiset jättämään kotimaansa, millaisia representaatioita heillä on pakolaismatkastaan sekä miten heidän aikeensa muuttaa Intiasta eteenpäin muotoutuvat Dharamsalassa ja miksi. Kiinnitän huomiota myös muuttoliikettä tukeviin puitteisiin Dharamsalassa sekä Tiibetistä Intiaan muuttaneiden haastateltavien aktiiviseen toimijuuteen. Tutkimusmenetelminä olen käyttänyt etnografisia kenttätyömenetelmiä, kuten havainnointia ja haastatteluja. Tein suurimman osan kenttätöistä vuosien 2009–2015 välillä Dharamsalassa, ja olin kentällä yhteensä noin kymmenen kuukautta. Dharamsalassa asuu noin 14 000 tiibetiläistä, mukaan lukien heidän hengellinen johtajansa 14. Dalai lama. Hän pakeni Intiaan delegaationsa kanssa vuonna 1959, noin kymmenen vuotta sen jälkeen, kun vasta perustettu Kiinan kansantasavalta alkoi ottaa haltuunsa tiibetiläisvaltaisia alueita. Nämä tapahtumat sysäsivät liikkeelle laajamittaisen tiibetiläisten diasporan. Intian hallitus antoi tiibetiläisten perustaa pakolaishallituksen Dharamsalaan, ja antoi sille lähes autonomisen aseman hallinnoida tiibetiläisyhteisöjä Intiassa. Dharamsala on myös lukuisten tiibetiläisten kansalaisjärjestöjen kotipaikka, ja sitä kutsutaan usein tiibetiläisten diasporan pääkaupungiksi. Dharamsala on monia näkökulmia avaava paikka tehdä muuttoliiketutkimusta, sillä erilaiset liikkuvuudet kohtaavat kaupungissa; sinne ei pelkästään muuteta Tiibetistä, vaan myös muutto eteenpäin Dharamsalasta on suosittua tiibetiläisten keskuudessa. Väitöskirjani nostaa esiin uudenlaisen esimerkin muuttoliikkeestä yhden tai useamman paikan läpi kohti muuttajan päämäärää Tiibetissä syntyneiden tiibetiläisten kontekstissa. Olen käyttänyt erilaisia, mutta toisiaan tukevia, teoreettisia ja käsitteellisiä lähestymistapoja Tiibetistä Dharamsalaan muuttaneiden tiibetiläisten muuttoliikkeen eri vaiheiden tarkastelussa. Väitöskirjani keskeisimmät käsitteet ovat kauttakulku (transit migration), pakolaismatka ja postkolonialistinen muuttoliiketutkimus erityisesti postkolonialistisen maantieteen kontekstissa. Näiden käsitteiden yhdistelmää voidaan soveltaa myös muiden vähemmistöjen tai pakolaisten useamman paikan tai maan kautta etenevään muuttoliikkeeseen Globaalissa Etelässä. Tulokseni osoittavat, että erityisesti tiibetiläisten muuttoliikettä Nepalin kautta Intiaan voidaan pitää kauttakulkuna ja että pakolaismatkalla Intiaan on myös tärkeä merkitys diasporassa asuville tiibetiläisille; matka Himalajan yli Intiaan on osa heidän kollektiivista identiteettiään pakolaisena. Muutto Intian kautta eteenpäin on kuitenkin monimutkaisempi ilmiö, sillä tiibetiläiset muuttavat Intiaan myös esimerkiksi halusta nähdä Dalai lama, saada koulutusta tiibetiläisten omista lähtökohdista käsin ja etsiä mahdollisuuksia itselleen, vaikka he myöhemmin muuttaisivatkin eteenpäin. Dharamsalassa on Tiibetistä saapuneita pakolaisia avustavia kansalaisjärjestöjä, jotka opettavat heille taitoja, kuten Englantia ja muita vieraita kieliä, joita tarvitaan myös mikäli he muuttavat eteenpäin. Lisäksi tutkimukseni osoittaa, että (post)kolonialistiset valtasuhteet, kuten heikko sosioekonominen asema ja rajalliset mahdollisuudet liikkuvuuteen, vaikuttavat tiibetiläisten poismuuttohalukkuuteen sekä Tiibetissä että Intiassa.